Population structure and genetic diversity of mango (Mangifera indica L.) germplasm resources as revealed by single-nucleotide polymorphism markers - Liang, Qingzhi; Pan, Hongbing; He, Xiaolong; Wang, Songbiao; Hou, Yuanhua; Xiao, Hua; Xu, Guangzhao; Yi, Runhua; Lin, Dongbo; Yang, Zhuanying (Frontiers in Plant Science, 2024)
Mango is a vital horticultural fruit crop and breeding is an essential strategy to enhance ongoing sustainability. Knowledge regarding population structure and genetic diversity in mango germplasm is essential for crop improvement. A set of 284 mango accessions from different regions of the world were subjected to high-throughput sequencing and specific-locus amplified fragment (SLAF) library construction to generate genomic single nucleotide polymorphism (SNP). After filtering, raw data containing 539.61 M reads were obtained. A total of 505,300 SLAFs were detected, of which, 205,299 were polymorphic. Finally, 29,136 SNPs were employed to dissect population structure, genetic relationships and genetic diversity. The 284 mango accessions were divided into two major groups: one group consisted mainly mango accessions from Australia, the United States, Cuba, India, Caribbean, Israel, Pakistan, Guinea, Burma, China and Sri Lanka, which belonged to India type (P1); the other group contained mango accessions from the Philippines, Thailand, Indonesia, Vietnam, Cambodia, Malaysia and Singapore, which belonged to Southeast Asian type (P2). Genetic diversity, principal component analysis (PCA), and population structure analyses revealed distinct accession clusters. Current results indicated that proposed hybridization occurred widely between P1 and P2; most of accessions (80.99%) were of mixed ancestry, perhaps including multiple hybridization events and regional selection, which merits further investigation.